(untitled) (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Sahid ZD, Syukur M, Maharijaya A, Nurcholis W. 2021. Polyphenol content and pharmacological activities of Capsicum frutescens and C. chinense genotypes. Biodiversitas 22: 3838-3843. Chili is a horticultural crop with potential as a functional food crop. This is because chili has beneficial biochemical parameters such as antioxidants, phenolics, flavonoids, and ?-glucosidase inhibitors. This study evaluated the biochemical parameters in twelve genotypes of two chili species (Capsicum frutescens and Capsicum chinense). Information from this research can be used as a reference in chili plant breeding activities which are directed as functional food plants. The method of measuring biochemical parameters using an ELISA reader with a modified method. Samples were measured with a microplate and repeated three times. The results that emerged from the ELISA reader were then converted with Microsoft Excel and analyzed using the R program. The results showed that the Capsicum chinense species (Habanero Fransisca) had the highest ?-glucosidase inhibitory activity (52.52%) compared to other genotypes of the Capsicum frutescens species. The highest TPC (19.42), TFC (2.51), and antioxidant FRAP (117.27) were shown by the pure line genotype F8 285290-290-2-2-4-4-1. The biochemical content of the chili genotypes tested was divided into three major groups. This grouping is not affected based on the species used. The correlation between antioxidants using the FRAP method with TFC (0.69) and TPC (0.83) is positive and significantly different. In conclusion, information on biochemical content can be used as a basis for developing genotypes, especially for the purposes of plant breeding activities in the future.